2021
DOI: 10.1111/een.13017
|View full text |Cite
|
Sign up to set email alerts
|

Some considerations on the terminology applied to dung beetle functional groups

Abstract: 1. Dung beetles are an important group of insects that use excrement for feeding and reproductive purposes. The interest of the scientific community in dung beetles is highlighted by the increasing number of investigations that use them as the focal group.2. In the last few years, several studies have used dung beetles as bioindicators and to study 'biodiversity-ecosystem functioning relationships' using functional traits. One of the most widely used functional traits in dung beetle studies is their reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Another interesting result regards dung beetle nesting behavior. We found that nester species, such as paracoprids and telecoprids, which show relocation behavior [ 78 ], prefer cow dung. On the contrary, non-nester species, which lay eggs directly in the dung pat where the entire development takes place, clearly prefer horse dung [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting result regards dung beetle nesting behavior. We found that nester species, such as paracoprids and telecoprids, which show relocation behavior [ 78 ], prefer cow dung. On the contrary, non-nester species, which lay eggs directly in the dung pat where the entire development takes place, clearly prefer horse dung [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to excrement utilization, dung beetles can be roughly classified into three main categories: dwellers, tunnellers, and rollers [ 25 , 76 , 77 ], but this classification may be imprecise [ 78 ]. Scarabaeids are typically tunnellers (i.e., they dig chambers more or less directly underneath the pat for feeding or breeding) or rollers (i.e., they form a ball of dung that can be rolled away from the pat and buried for feeding or breeding), whereas most aphodiids are dwellers (i.e., they feed in the dung pat as adults and lay eggs within or under the dung mass where they undergo larval development and do not construct nests) [ 25 , 46 , 76 , 77 ], but there are aphodiids that construct more or less elaborate pedotrophic nests [ 78 ]. In our samples, the only aphodiid species that could not be classified as dwellers were Colobopterus erraticus , Acrossus rufipes , and Bodilopsis rufa [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in abundance was mostly due to the very high abundance values attained by the scarabaeid Onthophagus fracticornis , which accounted for more than 90% of the total dung beetles collected in the grasslands at 1700–1850 m and some 80% at 1850–2000 m. Among the aphodiids, Bodilopsis rufa was particularly abundant (some 14% of total captured individuals) in the grassland habitat of the highest belt. These two species are eurytopic dung beetles with wide elevational ranges, and the ability of B. rufa to dig pedotrophic nests [ 78 ] may make this species a superior competitor compared to other aphodiids. The very high abundance of dung beetles observed in the 1700–1850 m can be associated with the distribution of grazing activities in the study area, where, during our sampling, cattle were very numerous and frequent in the pastures located at 1700–1800 m, allowing a larger availability of trophic sources to exist here.…”
Section: Discussionmentioning
confidence: 99%
“…The species were recorded as present or absent in each sampling plot. We classified the Scarabaeidae and Geotrupidae species according to their nesting behavior in 'non-nesters' (laying eggs in the dung), 'paracoprids' (laying eggs in dung buried under the excrement) with the help of the specialized literature (Klemperer 1980;Rojewski 1983;Zunino and Barbero 1990;Hanski 2016) and the revisions proposed by Tonelli (2021). All the data were transmitted to the Swiss database (info fauna-CSCF; distributional maps available here: https://lepus.unine.ch/carto/).…”
Section: Samplingmentioning
confidence: 99%